A History of the University in Europe, Vol. I Universities in the Middle Ages, ed. Hilde de Ridder-Symoens, Cambridge 1992, ss. 506. - Żołądź, Dorota (Biuletyn Historii Wychowania, 1995)
A History of the University in Europe, Vol. I Universities in the Middle Ages, ed. Hilde de Ridder-Symoens, Cambridge 1992, ss. 506.